The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17522/balikesirnef.373424
|View full text |Cite
|
Sign up to set email alerts
|

Scratch Yazılımının Öğrencilerin Bilgisayarca Düşünme Becerilerine Etkisi

Abstract: -The aim of this study is to determine the correlation between the scores of the computational thinking skills scale (CTSS) and the achievements of students' who took the Scratch programming education given within the scope of the course, Information & Communication Technology and Software and to investigate the effect of scratch education on the CTSS scores. In this quantitative study, the CTSS scores, the cumulative grade point averages (CGPA) of the students and the exam scores of the course were used. Befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 26 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…Kontrol grubunda yer alan özel yetenekli öğrencilere verilen blok tabanlı kodlama eğitiminin BİD becerilerinin gelişimine olumlu etki ettiği söylenebilir. Alan yazında, Yünkül, Durak, Çankaya, Mısırlı (2017) ve Dinci, (2021)' nin çalışmaları araştırma bulgusunu desteklemektedir. Yünkül vd.…”
Section: Tartişma Ve Sonuçunclassified
“…Kontrol grubunda yer alan özel yetenekli öğrencilere verilen blok tabanlı kodlama eğitiminin BİD becerilerinin gelişimine olumlu etki ettiği söylenebilir. Alan yazında, Yünkül, Durak, Çankaya, Mısırlı (2017) ve Dinci, (2021)' nin çalışmaları araştırma bulgusunu desteklemektedir. Yünkül vd.…”
Section: Tartişma Ve Sonuçunclassified
“…Similarly, it was found that STEM and coding education were interrelated areas and affected each other. As a result of Yünkül, Durak, Çankaya and Mısırlı (2017) studies, it was found that EĞİTİM TEKNOLOJİSİ Kuram ve Uygulama there was a high level of relationship between computational skill thinking skills and programming skills and that students with high computational thinking skills were also successful in programming. Secondary school students' self-efficacy perception levels for block-based coding education affect (14%) the total variance of the total variance together with the skill level and STEM skill level.…”
Section: öZmentioning
confidence: 99%
“…Günümüzde okul uygulamaları yanında, akademik alanda da bilgi-işlemsel düşünme becerilerine odaklandığı görülmektedir. Araştırmalar kapsamında bilgi-işlemsel düşünme, analitik düşünme, mantıksal düşünme, program-lama ve akademik başarı arasında pozitif ilişkiler olduğunu gösteren akademik çalışmalar söz konusudur (Baratè, Ludovico ve Mangione, 2016;Sebetci ve Aksu, 2014;Yünkül, Durak, Çankaya ve Mısırlı, 2017). Yine blok tabanlı kodlama uygulamalarının problem çözme (Begosso ve da Silva, 2013), mantıksal ve matematiksel düşünmeyi geliştirme (Taylor, Harlow ve Forret, 2010) üzerinde olumlu etkisi olduğunu gösteren araştırma bulguları bulunmaktadır.…”
Section: Introductionunclassified